2011
DOI: 10.5787/33-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Revolution in Military Affairs, Missile Defence and Weapons in Space: The Us Strategic Triad

Abstract: American plans for Missile Defence (MD) and the weaponisation of space should be analysed in the larger framework of the contemporary Revolution in Military Affairs (RMA).1 Soviet military analysts have written about this revolution from as early as the 1970s, but it was the application of information age technology (IT) in the 1991 Gulf War that captured the imagination of military planners and policy makers, especially in the US. The US is actively pursuing an RMA, conceptualised as integrating new IT into w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This is when new technologies like stealth and precision guided munitions thrived, and new operational concepts were developed. It was the beginning of the so-called, network centric warfare, information operations and wider developments of the C4ISR (Pretorius, 2011). A new RMA emerged against weaker enemies.…”
Section: The "American'' Rmamentioning
confidence: 99%
See 1 more Smart Citation
“…This is when new technologies like stealth and precision guided munitions thrived, and new operational concepts were developed. It was the beginning of the so-called, network centric warfare, information operations and wider developments of the C4ISR (Pretorius, 2011). A new RMA emerged against weaker enemies.…”
Section: The "American'' Rmamentioning
confidence: 99%
“…The former might not have posed any problems when fighting against terrorists, but according to Wortzel (2008), an adversary such as China could easily disrupt these domains. Moreover, aside from the fact that space enables the current US RMA, it is at the same time seen as an element that increases vulnerability (Pretorius, 2011). Besides, US capabilities have not been yet tested in an all-out war and under no circumstances could it be suggested that the US would easily win a potential war with China and/or Russia due to its technological advantages or its ongoing RMA (Bitzinger, 2017).…”
Section: The "American'' Rmamentioning
confidence: 99%